IMPLIKASI YURIDIS ATAS PUTUSAN MAHKAMAH KOINSTITUSI TENTANG PENYELENGGARAAN PEMILIHAN UMUM SERENTAK TAHUN 2019 - Widaningsih Widaningsih (Jurnal Cakrawala Hukum, 2014)
The Constitutional Court (MK) granted a judicial review of law no. 42 Year 2008 regarding the presidentialelection proposed by Yusril Ihza Mahendra and Effendi Gazali with Community Coalition for Election Unison.The Court decided that legislative and presidential elections would be conducted simultaneously inGeneral Election in 2019. The proposed Articles were Article 3 Paragraph ( 5 ), Article 9, Article 12Paragraph ( 1 ) and ( 2 ), Article 14, Paragraph ( 2 ), and Article 112. With the granting of this lawsuit, theLegislature election and the 2019 presidential election would be held simultaneously so that there was nothreshold for the candidates of president and vice president. Legislative election and the 2014 presidentialelection would be implemented separately. Election problems like political and democracy costs that weregreater quickly could be solved properly by carrying on simultaneous elections. Concurrent elections did notonly lighten the cost of the election, but also created time and energy efficiency as well as reduced the potentialoutbreak of a horizontal conflict as what often happened among the candidates parties who were competing.